Two‐port ring‐shaped dielectric resonator‐based diversity radiator with dual‐band and dual‐polarized features. Issue 2 (1st October 2019) - Bharti, Gagandeep; Kumar, Dharmendra; Gautam, Anil K.; Sharma, Anand
Abstract: In this article, a two‐port dielectric resonator (DR)‐based multi‐input multi‐output (MIMO) antenna is designed and examined. Some of the vital characteristics of designed antenna are: (a) modified plus shaped aperture fed ring DRA provides dual frequency bands, which can able to make proposed radiator useful for wireless LAN (2.4 GHz) and WiMAX frequency bands (3.3 GHz); (b) conversion of cylindrical to ring shaped DRA enhance the impedance bandwidth of both the operating band; (c) defected ground structure as well as using the idea of changing polarization at two different ports improves the isolation more than 20 dB in the working frequency range. For confirming the computer‐generated results, prototype of proposed two‐port radiator is fabricated. After observing the measured outcomes, it can be confirmed that the proposed antenna works over dual frequency ranges, that is, 2.3‐2.9 GHz/3.4‐4.0 GHz and it also creates CP waves in between 3.45 and 3.8 GHz. Far field and diversity parameters confirm that the designed radiator can be used in MIMO communication system.